Pilot Testing a Bedside Patient Safety Display to Increase Provider Awareness of the 'Hidden Hazards' of Catheters and Wounds. (October 2020) - Ameling, Jessica; Greene, M Todd; Quinn, Martha; Meddings, Jennifer
Abstract : Background: Urinary catheters, vascular catheters, and wounds, such as pressure injuries are often hidden from view under gowns and sheets (ie, out of sight, out of mind), contributing to prolonged catheter use, infections, delayed interventions, and diagnostic errors for symptoms (eg, fever or delirium) related to catheters and wounds. We developed and pilot tested a digital bedside Patient Safety Display of catheter and wound information to improve awareness by rounding providers (ie, physicians and advanced practice providers, APPs). Methods: The display development was informed by clinical observations of provider rounds and nurse handoffs, interviews, and iterative prototype testing with clinicians in simulated cases using catheterized mannequins with wounds. The display reports the presence and duration of urinary and vascular catheter use, urinary catheter indication, and wound presence and severity, from real-time mandatory nurse documentation in the electronic medical record (Fig. 1). We conducted a pilot study in a tertiary-care medical-surgical step-down unit with 20 private rooms, including a preintervention period and a postintervention period including 10 rooms without the display (control rooms) and 10 rooms with the display (intervention rooms). We surveyed individual providers directly after rounds to assess their awareness of their patients' catheters and wounds compared to medical record documentation. We also assessed display utility and usability from postintervention clinician interviews and we identified major themes using an adapted grounded theory approach. Results: In total, 787 surveys were completed: 681 medicine service with 89% response rate, 106 surgery service with 47% response rate; 363 preintervention surveys, and 424 postintervention surveys. The surveys involved 176 unique patients and 47 unique providers. Among all 787 patient encounters, 156 (19.8%) had a transurethral indwelling urinary catheter (Foley), 314 (39.9%) had a central venous catheter (including PICCs), and 247 (31.4%) had at least 1 pressure injury. Figure 2 summarizes provider awareness of catheters and pressure injuries when present as assessed for patients in the preintervention and postintervention periods. Moreover, 13 clinician postintervention interviews yielded preliminary themes regarding the display's benefits and limitations (Fig. 3). Conclusions: In this pilot study of a novel Patient Safety Display, although provider awareness of Foley catheters, CVCs, and pressure injuries appeared higher for patients in the intervention rooms compared to awareness as measured in the preintervention rooms and/or postintervention control rooms, most of these comparisons did not meet statistical significance. Clinicians varied widely in their personal assessments of the display as a useful tool for improving awareness and prompting discussion about catheters and wounds. Funding: This work was funded by the Agency for Healthcare Research and Quality (AHRQ) grant P30HS024385. Dr. Meddings' effort was initially partially funded by concurrent support from AHRQ (K08 HS19767). Disclosures: Dr. Meddings has reported receiving honoraria for lectures and teaching related to prevention and value-based purchasing policies involving catheter-associated urinary tract infection. The remaining authors report no conflicts of interest.